Case report of snaring-assisted TAVR under cerebral embolic protection: the “Chaperone” with “Top Hat” technique - Medda, Massimo; Casilli, Francesco; Bande, Marta; Tespili, Maurizio; Donatelli, Francesco (Frontiers in Cardiovascular Medicine, 2023)
Symptomatic severe aortic stenosis (AS) in patients with intermediate-to-high surgical risk is currently being treated with transcatheter aortic valve replacement (TAVR). We present a case of a TAVR in a severe calcific AS with porcelain aorta and ‘gothic’ aortic arch. Pre-operative thoraco-abdominal computed tomography angiography showed also severe calcification at the sinotubular junction with protruding huge calcified nodules extending in ascending aorta and multiple calcific stenosis of both iliac-femoral vessels, severely tortuous. The choice of the interventional access was not easy and the high risk of an acute intra-procedural brain event guided the procedural planning. To our knowledge, this is the first case of TAVR with complete cerebral protection with Triguard system device and ‘snaring-assisted’ valve advancement.